Fiber optic monitoring of an anti-slide pile in a retrogressive landslide - Zhang, Lei (2023)
Anti-slide piles are one of the most important reinforcement structures against landslides, and evaluating the working conditions is of great significance for landslide mitigation. The widely adopted analytical methods of pile internal forces include cantilever beam method and elastic foundation beam method. However, due to many assumptions involved in calculation, the analytical models cannot be fully applicable to complex site situations, e.g. landslides with multi-sliding surfaces and pile-soil interface separation as discussed herein. In view of this, the combination of distributed fiber optic sensing (DFOS) and strain-internal force conversion methods was proposed to evaluate the working conditions of an anti-sliding pile in a typical retrogressive landslide in the Three Gorges reservoir area, China. Brillouin optical time domain reflectometry (BOTDR) was utilized to monitor the strain distribution along the pile. Next, by analyzing the relative deformation between the pile and its adjacent inclinometer, the pile-soil interface separation was profiled. Finally, the internal forces of the anti-slide pile were derived based on the strain-internal force conversion method. According to the ratio of calculated internal forces to the design values, the working conditions of the anti-slide pile could be evaluated. The results demonstrated that the proposed method could reveal the deformation pattern of the anti-slide pile system, and can quantitatively evaluate its working conditions.